Microbial Toxins Methods and Protocols - Holst, Otto.; Holst, Otto. (Methods in Molecular Biology,, 2011)
Interest in the field of microbial toxins is ever growing and spreading across a broad spectrum of scientific disciplines. In an effort to supplement the available reference texts on toxins, Microbial Toxins: Methods and Protocols includes protocols on mold fungus toxins, with some focus on aflatoxins. Intended to support a wide variety of researchers, Microbial Toxins: Methods and Protocols presents the reader with biological, chemical, physical, and medical approaches, as well as state-of-the-art research techniques. Divided into three convenient sections, this detailed volume covers bacterial protein toxins, endotoxins, and mold fungus toxins. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible, Microbial Toxins: Methods and Protocols seeks to serve both professionals and novices with its well-honed methodologies in an effort to further our knowledge of this essential field.